Health care providers' attitudes towards termination of pregnancy: A qualitative study in South Africa - Orner Phyllis; Stinson Kathryn; Harries Jane (BMC, 2009)
Abstract Background Despite changes to the abortion legislation in South Africa in 1996, barriers to women accessing abortion services still exist including provider opposition to abortions and a shortage of trained and willing abortion care providers. The dearth of abortion providers undermines the availability of safe, legal abortion, and has serious implications for women's access to abortion services and health service planning. In South Africa, little is known about the personal and professional attitudes of individuals who are currently working in abortion service provision. Exploring the factors which determine health care providers' involvement or disengagement in abortion services may facilitate improvement in the planning and provision of future services. Methods Qualitative research methods were used to collect data. Thirty four in-depth interviews and one focus group discussion were conducted during 2006 and 2007 with health care providers who were involved in a range of abortion provision in the Western Cape Province, South Africa. Data were analysed using a thematic analysis approach. Results Complex patterns of service delivery were prevalent throughout many of the health care facilities, and fragmented levels of service provision operated in order to accommodate health care providers' willingness to be involved in different aspects of abortion provision. Related to this was the need expressed by many providers for dedicated, stand-alone abortion clinics thereby creating a more supportive environment for both clients and providers. Almost all providers were concerned about the numerous difficulties women faced in seeking an abortion and their general quality of care. An overriding concern was poor pre and post abortion counselling including contraceptive counselling and provision. Conclusion This is the first known qualitative study undertaken in South Africa exploring providers' attitudes towards abortion and adds to the body of information addressing the barriers to safe abortion services. In order to sustain a pool of abortion providers, programmes which both attract prospective abortion providers, and retain existing providers, needs to be developed and financial compensation for abortion care providers needs to be considered.